2022
DOI: 10.3389/fgene.2021.778788
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Transcriptome Analyses of Gayal (Bos frontalis), Yak (Bos grunniens), and Cattle (Bos taurus) Reveal the High-Altitude Adaptation

Abstract: Gayal and yak are well adapted to the local high-altitude environments, yet the transcriptional regulation difference of the plateau environment among them remains obscure. Herein, cross-tissue and cross-species comparative transcriptome analysis were performed for the six hypoxia-sensitive tissues from gayal, yak, and cattle. Gene expression profiles for all single-copy orthologous genes showed tissue-specific expression patterns. By differential expression analysis, we identified 3020 and 1995 differentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 114 publications
(152 reference statements)
2
7
0
Order By: Relevance
“…, the greater the elevation span, the greater the number of differentially expressed unigenes ( Figure 2B ). This is consistent with other studies on Potentilla L. ( Ma et al., 2015 ), Bos L. ( Ma et al., 2022a ) and other species of Rhododendron ( Liu et al., 2022b ). In this sense, one could hypothesize that along a mountain cline, with increasing elevation, the stresses caused by environmental factors become more severe, and as adaptation of species to these changing environments additional genes are activated, also known as environmental adaptation ( Sun et al., 2018 ; Wang et al., 2021b ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…, the greater the elevation span, the greater the number of differentially expressed unigenes ( Figure 2B ). This is consistent with other studies on Potentilla L. ( Ma et al., 2015 ), Bos L. ( Ma et al., 2022a ) and other species of Rhododendron ( Liu et al., 2022b ). In this sense, one could hypothesize that along a mountain cline, with increasing elevation, the stresses caused by environmental factors become more severe, and as adaptation of species to these changing environments additional genes are activated, also known as environmental adaptation ( Sun et al., 2018 ; Wang et al., 2021b ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, by comparing the high and low elevational samples of different organs, i.e., late flower buds and early leaf buds, the number of significantly DEUs in their respective comparisons showed a positive correlation with the magnitude of the elevational distance, i.e., the greater the elevation span, the greater the number of differentially expressed unigenes (Figure 2B). This is consistent with other studies on Potentilla L. (Ma et al, 2015), Bos L. (Ma et al, 2022a) and other species of Rhododendron (Liu et al, 2022b). In this sense, one could hypothesize that along a mountain cline, with increasing elevation, the stresses caused by environmental factors become more severe, and as adaptation of species to these changing environments additional genes are activated, also known as environmental adaptation (Sun et al, 2018;Wang et al, 2021b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies of yak heart at the tissue and molecular levels have shown that adaptation to the plateau environment mainly involves changes in metabolism, immune function, and adaptation to hypoxia [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, results of genome analysis indicated that the CAMK2B gene function to regulate gastric acid secretion in the rumen would be positively selected in the pathway of volatile fatty acid (VFA) production in yaks ( Allen et al., 2009 ; Weimer et al., 2009 ; Qiu et al., 2012 ). Based on the comparative transcriptome analysis of 6 tissues collected from cattle and yaks, Ma et al. (2021) found that among differential genes related to energy metabolism, TPI1 (triosephosphate isomerase) was up regulated and G6PC (the gene encoding glucose-6-phosphatase) was downregulated.…”
Section: Higher Efficiency Of Energy Acquisition-anatomical Behaviora...mentioning
confidence: 99%